Characterization of Eight Novel Spiroleptosphols from Fusarium avenaceum - Westphal, Klaus Ringsborg; Werner, Manuela Ilse Helga; Nielsen, Katrine Amalie Hamborg; Sørensen, Jens Laurids; Andrushchenko, Valery; Winde, Jacob; Hertz, Morten; Jensen, Mikkel Astrup; Mortensen, Mathilde Lauge; Bouř, Petr; Sondergaard, Teis Esben; Wimmer, Reinhard (Molecules, 2019)
Chemical analyses of Fusarium avenaceum grown on banana medium resulted in eight novel spiroleptosphols, T1, T2 and U-Z (1-8). The structures were elucidated by a combination of high-resolution mass spectrometric data and 1- and 2-D NMR experiments. The relative stereochemistry was assigned by 1H coupling and NOESY/ROESY experiments. Absolute stereochemistry established for 7 by vibrational circular dichroism was found analogous to that of the putative polyketide spiroleptosphol from Leptosphaeria doliolum.
Keywords: Chemical Phenomena; vysokoúčinná kapalinová chromatografie; Molecular Structure; Metabolic Networks and Pathways; Fusarium; magnetická rezonanční spektroskopie; metabolické sítě a dráhy; molekulární struktura; Chromatography, High Pressure Liquid; Magnetic Resonance Spectroscopy; Spiro Compounds; spirosloučeniny; chemické jevy